ANALYSIS OF FACTORS INFLUENCING COMMUNITY-BASED HYPERTENSION CONTROL EFFORTS - Kurniawan, Aditya; Arini, Liss Dyah Dewi (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Hypertension is still a big challenge in Indonesia. Hypertension is a condition that is often found in health services. The urgency of this research is the large number of hypertension patients at the Ngoresan Health Center, Surakarta and has increased almost every year. The objective problem in this study is that the number of patients with hypertension increases from year to year, so research is needed on the relationship of knowledge, attitudes and family support with efforts to control hypertension. The importance of this research is as an effort to control hypertension which continues to increase from year to year by means of a questionnaire interviews and distribution of brochures/pamphlets with the aim of approaching the community. The purpose of this study was to analyze the factors that influence efforts to control hypertension in patients at the Ngoresan Health Center, Surakarta. Method. The stages of achievement in this study are for the approach used in this study, namely cross sectional. The sample in this study amounted to 86 respondents. Sampling technique with accidental sampling method based on inclusion and exclusion criteria. The statistical test used is Chi-Square with (α=0.05). Result and Analysis. The results of this study indicate that there is a relationship between knowledge and efforts to control hypertension in the elderly with a p-value = 0.003 (<α=0.05), there is a relationship between attitudes and efforts to control hypertension in the elderly with a p-value = 0.011 ( <α=0.05) and there is a relationship between family support and efforts to control hypertension in the elderly with a p-value = 0.034 (<α=0.05). Discussion. There is a relationship between knowledge, attitudes and family support with efforts to control hypertension.